The impact of oil on a developing country : the case of Nigeria - Ikein, Augustine A. (New York : Praeger, 1990)
This study provides a comprehensive and balanced analysis of the impact of the oil industry on a particular developing country--Nigeria--over a period of 32 years. Arguing that previous studies on the oil industry in developing countries have tended to focus only on the economic significance of oil, ignoring its societal costs, Ikein uses a multidimensional approach that enables him to identify the linkage between the performance of the oil industry and the pattern of Nigeria's national and regional development.
Includes bibliographical references (p. [269]-288) and index.
oif 11/02/15
Loan
Keywords: Petroleum industry and trade; Oil industries; Economic conditions; Nigeria; Nigeria; Nigeria